Inventory of Plants Used in the Krowe Ethnic Ceremony of Pogon Village - Erista, Natalia (EduMatika: Jurnal MIPA, 2022)
The inventory of plants used in the traditional ceremony of the ethnic Krowe of Pogon Village. This study aims to find out about the types of plants, the function of plants and the meaning of plants used in the ethnic traditional ceremony of Krowe Pogon Village. The method used is a qualitative descriptive method. Determination of respondents using a random or random purposive method. The types of plants used in traditional ceremonies are done by describing the morphology of these plants. The results showed that the plants used in traditional ceremonies in Pogon plants Village consisted of 9 species grouped in 6 families namely Musaceae, Arecaceae, Piperaceae, Arecaceae, Moraceae, Moraceae, Apocynaceae, Poaceae, Graminea. These types of plants have their own functions and meanings in every traditional ceremony such as Mu’u / Pisang, and Wua / Pinang function as a sign to propose a girl,  Kabor / coconut for the cooling of the grave that has been, built, Huler / Aware cooling the two couples when returning from the church, Bao / Bayan or Rita / Pulai serves to hang the umbilical cord, Peli / Bamboo to close the body in the grave before being piled up on the ground and the Pare Weran / Rice to feed ancestral spirits. The meaning of plants used in traditional ceremonies is the purity of love and loyalty (traditional marriage ceremonies), cooling (death and marriage), as a protective tree and gives coolness to a baby (traditional ceremony of birth), calm (traditional ceremony of death)